Structural, magneto transport and magnetic properties of Ruddlesden–Popper La2-2xSr1+2xMn2O7 (0.42≤x≤0.52) layered manganites - Ajay Kumar Saw; Shalabh Gupta; Vijaylakshmi Dayal (AIP Advances, 2021)
The magneto transport of Ruddlesden–Popper, La2-2xSr1+2xMn2O7 (0.42≤x≤0.52), 2-dimensional bilayered manganites have been investigated in a broad temperature range. The samples have been synthesized using the solid-state reaction method. Rietveld refinement of the X-ray diffraction data indicates the tetragonal structure formation with I4/mmm space group. The resistivity curves of the samples present a general characteristic of metal-insulator (MI) transition at certain temperature (TMI). Besides, for samples with x = 0.48, 0.50, and 0.52, at a certain temperature (TCO) well below TMI the charge ordering is also evident. Furthermore, the samples display a shallow upturn in resistivity below Tmin due to the Kondo like spin scattering effect, weak localization and electron-phonon interaction. The high temperature semiconducting (T>TMI) region, the resistivity curve follows the 3D Mott’s variable hopping transport mechanism. The overall suppression of resistivity accounts for a substantial magnetoresistance by applying a magnetic field and the characteristic change in TMI, TCO, and Tmin are discussed. Temperature-dependent magnetization demonstrates the suppression of ferromagnetism and evident of antiferromagnetic nature with an apparent charge ordering with increasing concentration of Sr2+.